1986
DOI: 10.1113/jphysiol.1986.sp016172
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation in sensitivity of suprachiasmatic and lateral geniculate neurones to 5‐hydroxytryptamine in the rat.

Abstract: SUMMARY1. Extracellular single-unit recordings were obtained from neurones in the suprachiasmatic nuclei (s.c.n.) of the rat (a putative circadian pace-maker), the ventral lateral geniculate nucleus (v.l.g.n.) and the hippocampus. These areas receive a 5-hydroxytryptamine (5-HT) innervation from the raphe nuclei. Recording of neuronal activity in the s.c.n., v.l.g.n. and the hippocampus revealed a diurnal variation in the response to the ionophoresis of 5-HT. This variation was manifest as a 2-3-fold increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(30 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…Thus, the extent of phase-shifting response could be influenced by postsynaptic, as well as by presynaptic, 5-HT-related actions, with the extent of a shift being determined by the circadian period of delivery of the nonphotic stimulus, as well as by the pattern of 5-HT release preceding the stimulus. Although a relationship between physiological change in 5-HT release and postsynaptic responsiveness to 5-HT has received little study, it is suggested that circadian fluctuations in postsynaptic neurophysiological and behavioral responses to 8-OH-DPAT (Mason, 1986;Currie and Coscina, 1993;Lu and Nagayama, 1996) may be keyed to rhythmic daily changes in 5-HT release modulating daily changes in 5-HT 1A receptor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the extent of phase-shifting response could be influenced by postsynaptic, as well as by presynaptic, 5-HT-related actions, with the extent of a shift being determined by the circadian period of delivery of the nonphotic stimulus, as well as by the pattern of 5-HT release preceding the stimulus. Although a relationship between physiological change in 5-HT release and postsynaptic responsiveness to 5-HT has received little study, it is suggested that circadian fluctuations in postsynaptic neurophysiological and behavioral responses to 8-OH-DPAT (Mason, 1986;Currie and Coscina, 1993;Lu and Nagayama, 1996) may be keyed to rhythmic daily changes in 5-HT release modulating daily changes in 5-HT 1A receptor sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, SCN neurons in brain slices show a circadian variation in sensitivity to serotonin in terms of firing rate, such that the neurons are more sensitive to inhibition of firing rate by serotonin in the subjective night (Mason, 1986). Besides the circadian rhythm of sensitivity to serotonin, the SCN also display a circadian rhythm in recovery from serotonin.…”
mentioning
confidence: 99%
“…Besides the circadian rhythm of sensitivity to serotonin, the SCN also display a circadian rhythm in recovery from serotonin. Mason (1986) demonstrated that the time of recovery after inhibition of neuronal activity was longer when serotonin was administered during the day-time than during the night.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent modulatory effects of BTS 54 505 on agonist-evoked responses were then routinely assessed using agonist ejection currents that elicited 50-80% maximal response. Electrophysiological recording, display and processing of discriminated signals was conventional (Mason, 1986). Discriminated neuronal activity was plotted as integrated firing rate histograms over successive 5 s epochs onto a chart recorder.…”
Section: Methodsmentioning
confidence: 99%